Effects of Beauveria bassiana (Hypocreales: Cordycipitaceae) on the midgut of the Chrysomya megacephala (Fabricius, 1794) (Diptera: Calliphoridae) maggots (Research, Society and Development, 2022)
Beauveria bassiana is an entomopathogenic fungus widely used in pest management. After contact with target organisms, fungal conidia germinate and colonize tissues and organs, causing death by starvation and/or septicemia. Chrysomya megacephala is an insect pest with worldwide distribution. Its larvae cause secondary myiasis in animals of interest, and adults are pathogen vectors. This study aimed to analyze the effects of the Ballvéria® biopesticide on the midgut of C. megacephala third-instar maggots. Four concentrations (1, 1.5, 2, and 4%) of the biopesticide were applied to an artificial diet, followed by conditioning of the maggots. Mortality data and samples for histological and ultrastructural analysis were collected every 24 h, for 144 h. Mortality data were analyzed using SPSS 25.0, and lethal concentrations (LC50 and LC90) were calculated using Probit regression. Concentrations of 2 and 4% resulted in mortality rates of 26 and 36%, respectively. LC50 and LC90 were estimated at 5.3 and 10.9%, respectively. Observational, histological, and ultrastructural analyses revealed the presence of tegumentary melanizations, conidia in the midgut, spacing in the basal labyrinth, degeneration of microvilli, absence of the peritrophic membrane, fungal extrusion on the external surface of the midgut, and dispersion of hyphae, conidiophores, and conidia close to muscle fibers. Internally, hyphae are located on microvilli and cell projections. Our data confirm that the Ballvéria® biopesticide causes cytotoxic effects in the midgut of C. megacephala maggots and can be used as a sustainable alternative in its biological control for Integrate Pest Management.